2019
DOI: 10.1371/journal.pone.0226331
|View full text |Cite
|
Sign up to set email alerts
|

Dietary habits of the black-necked swan Cygnus melancoryphus (Birds: Anatidae) and variability of the aquatic macrophyte cover in the Río Cruces wetland, southern Chile

Abstract: The black-necked swan Cygnus melancoryphus is an aquatic herbivorous bird whose dietary habits depend on the dominance and accessibility of macrophyte banks in shallow areas of coastal and limnetic wetlands in southern South America. The swans from the Río Cruces wetland in southern Chile (ca. 39°S) feed mainly on the macrophyte Egeria densa from the water column between depths from less than 0,5 and 2,0 m. A micro- histological analysis of black-necked swan feces (N = 152) collected during six sampling occasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
2
0
1
Order By: Relevance
“…In other studies, they found that swans show preference by less shallower and with some degree of eutrophication (Corti 1996;Cursach et al 2015). However, C. melancoryphus did not show differences between sites with regards to the feeding behaviour, because it is an opportunistic consumer that uses those habitats where the access to feed is easier and there is more abundance of food (Corti 1996;Corti & Schlatter 2002;Figueroa-Fábrega et al 2006;Velásquez et al 2019;Norambuena et al 2023).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In other studies, they found that swans show preference by less shallower and with some degree of eutrophication (Corti 1996;Cursach et al 2015). However, C. melancoryphus did not show differences between sites with regards to the feeding behaviour, because it is an opportunistic consumer that uses those habitats where the access to feed is easier and there is more abundance of food (Corti 1996;Corti & Schlatter 2002;Figueroa-Fábrega et al 2006;Velásquez et al 2019;Norambuena et al 2023).…”
Section: Discussionmentioning
confidence: 92%
“…It is possible to think that both species apply a strong suppression in the proliferation of aquatic vegetation in the salt pools, being this really beneficial for the workers. However, there is not much knowledge about the behaviour patterns of these swans and it is necessary to know how many time they devote to each one of these behaviours (Corti 1996;Brewer & Vilina 2002;Silva & Brewer 2007;Echevarria et al 2013;Cursach et al 2015;Velásquez et al 2019). It is crucial to understand their role as ecosystem service providers.…”
Section: Introductionmentioning
confidence: 99%
“…1A). Las tres primeras se alimentan de Limnobium laevigatum (Velásquez et al 2018(Velásquez et al , 2019a(Velásquez et al , 2019b; en el primer trabajo citado (Velásquez et al 2018) los autores la consideran importante en la alimentación de aves, ya que la incluyen en un catálogo microhistológico, para determinar plantas a partir de epidermis encontradas en sus fecas. Couve & Vidal (2004) Las condiciones del hábitat de Limnobium laevigatum, distinguen a la especie como una buena indicadora de eutrofización, especialmente con materia orgánica (Saíz et al 1980, Palma et al 1987.…”
Section: Discussionunclassified